Gen Z Menyukai Makanan Siap Saji - Wicaksono, Febryan; Pramudito, Pramudito; Nurbaeti, Nurbaeti (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan Digital, 2026)
This study aims to analyze the factors influencing Generation Z’s preference for fast food by examining the roles of taste preference, convenience, price value, and digital influence. A quantitative research approach was employed using a survey method involving 200 Generation Z respondents who had consumed fast food. Data were analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that all independent variables have a positive and significant effect on Generation Z’s fast food preference. Convenience was identified as the strongest predictor, indicating that accessibility, efficiency, and ease of purchase are primary considerations among young consumers. Furthermore, digital experience strengthens the relationship between consumption-related factors and fast food preference, demonstrating the important role of digital ecosystems in shaping contemporary food choices. This study contributes to consumer behavior literature by highlighting that Generation Z’s preference for fast food is not solely determined by product attributes but also by economic value, lifestyle demands, and digital interactions. The findings provide practical implications for the food industry in developing consumer-oriented strategies through product innovation, value creation, and digital marketing optimization. Keywords: Generation Z, fast food, consumer preference, food consumption behavior, digital influence, PLS-SEM